Unmet need for treatment-seeking from public health facilities in India: An analysis of sociodemographic, regional and disease-wise variations - Rajaram Yadav; Jeetendra Yadav; Chander Shekhar (Public Library of Science (PLoS), 2022)
Treatment-seeking behaviour is closely associated with the health status of individuals and countries. About 800 million people have no access to health services in the developing world. Though the situation has been improving, the inequalities across geographical regions, socioeconomic status, and disease types continued to persist. The available literature suggests research gaps in examining the unmet need for treatment-seeking from public health facilities across sociodemographic characteristics, regions, and specific diseases. Data for this study comes from the three rounds of National Sample Survey (NSS) (2004, 2014, 2018). We applied descriptive, bivariate, and multivariable analysis to investigate the unmet need for treatment-seeking for public health facilities across sociodemographic characteristics, regions, and specific diseases between 2004 and 2018. The unmet need for treatment-seeking from public health facilities remained high at 60% in 2004 to 62% in 2018. However, the proportion of respondents who did not seek treatment has reduced 12% to 3% from 2004 to 2018. In states like Andhra Pradesh, Madhya Pradesh, Maharashtra, Punjab, Telangana, Uttar Pradesh, and West Bengal, the unmet need for treatment-seeking from public health facilities was more than 60% in 2018. For 2018, the quality of services at public health facilities was the main reason for showing a higher unmet need for treatment-seeking in the richer MPCE quintiles. On the other hand, the ailment not considered serious as the main reason for the unmet need for treatment-seeking from any sources has got nearly doubled from 36% in 2004 to 71% in 2018. This study concludes that improving the availability of various kinds of services at public health facilities should be a priority under India's universal health coverage program. Education plays a vital role in treatment-seeking. Thus, there is an urgent need for increasing awareness among people for treatment-seeking. Ensuring a minimum quality of health care services and reducing long waiting timing would reduce the apathy to receive services from the public health facilities.